The Role of African Regional Organisations in the Management of Electoral Conflicts. A Case of SADC and ECOWAS - Moyo, Nonjabulo Mhambi (Eastern Mediterranean University EMU, 2017)
Elections have become a common phenomenon in the modern politics of the post-colonial Africa and are being used as tools for peaceful transition of power and the consolidation of democracy This has however proven to be a difficult process including many actors and as such regional organisations in Africa have become important players in the management of elections. This thesis analyses the role played by the South African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in the management of electoral conflicts within their respective regions. The Democratic Peace theory is used as a conceptual framework of analysis particularly with regards to issues of democracy, conflicts and peace. Electoral malpractices are among the challenges to the democratization process in Africa and have resulted in the lack of trust towards the electoral systems. The study identifies and analyses the mechanism’s adopted to address electoral related conflicts these include the Protocol on Democracy and Good Governance and the Principles and Guidelines Governing Democratic Elections. Using Cote d’Ivoire, Gambia, Lesotho and Zimbabwe as cases studies, the study findings indicate considerable progress in the management of electoral conflicts by ECOWAS and SADC. The interventions by ECOWAS have resulted in the belief that the application jus en bello has shifted in Africa whilst the SADC interventions indicate a softer and diplomatic approach. Keywords: Conflict management, regional organisations, elections, democracy

ÖZ: Seçimler sonrası sömürge Afrika modern siyaset ortak bir fenomen haline gelmiştir ve araçları olarak güç huzurlu geçiş ve bu ancak birçok aktör de dahil olmak üzere zor bir süreç olduğu ispatlanmıştır demokrasi sağlamlaştırılması için kullanılmakta olan ve bu nedenle Afrika'da bölgesel örgütlere seçimleri yönetiminde önemli oyuncular haline gelmiştir. Bu tez Güney Afrika Kalkınma Topluluğu (SADC) ve ekonomik topluluk, Batı Afrika Birleşik Devletleri (ECOWAS) onların kendi bölgeleri içinde seçim çatışmaların Yönetimi'nde oynadığı rolü inceliyor. Demokratik barış teorisi analiz özellikle açısından demokrasi, çatışmalar ve barış konularında kavramsal bir çerçeve olarak kullanılır. Seçim dogmayı zorluklar için Afrika demokratikleşme sürecinde arasındadır ve seçim sistemleri doğru güven eksikliği sonuçlandı. Çalışma tanımlar ve mekanizması'nın kabul edilen adres seçim analizleri ile ilgili çatışmalar bu protokolü demokrasi ve iyi yönetişim ve ilkeler ve kurallar yöneten demokratik seçimler içerir. Fildişi Sahilleri, Gambiya, Lesotho ve Zimbabve olarak vaka çalışmaları, kullanarak çalışma bulgular ECOWAS ve SADC seçim çatışmalarla yönetiminde önemli ilerleme göstermektedir. Müdahaleler ECOWAS tarafından SADC müdahaleler daha yumuşak ve diplomatik bir yaklaşım gösterir iken uygulama jus tr bello Afrika'da kaymıştır inancı içinde sonuçlandı. Anahtar kelimeler: çatışma yönetimi, bölgesel örgütlere, seçimler, demokrasi
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2017. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Conflict management; regional organisations; elections; democracy; Political Science and International Relations; Elections - Democracy - Africa; Election management bodies - Africa; Electoral Conflicts, Managements - South African Development Community (SADC) - Community of West African States (ECOWAS); Democratic Elections; Good Governance